Symbols and Metaphors of Ceramic Sculpture Receptacles - Donkor, Evans Kwadwo; Navei, Nyamawero; Addae, Alexander (Abdul Media Literasi, 2024)
In Africa, the production of ceramic sculpture receptacles is a common artistic practice. This artistry has attracted a plethora of historical, cultural, archaeological, and ethnographic studies. Such studies have revealed some of these African ceramic sculpture receptacles' metaphorical, philosophical, social, and cultural contexts. However, the paucity of literature on the symbols and metaphors of the ceramic sculpture receptacles produced at Takoradi Technical University (TTU) in Ghana provides a research gap. The current study, therefore, sought to examine selected ceramic sculpture receptacles from the Ceramic Design Technology Department of TTU to reveal their symbolic and metaphorical connotations from the indigenous Ghanaian cultural context. The study utilised a qualitative research approach and a descriptive research design. Twelve (12) ceramic sculpture receptacles were purposively sampled, and triangulation of instruments, including non-participant observation, personal interviews, and document reviews, were used to elicit interpretative data from thirteen experts (lecturers & students of TTU), who were all practicing artists. The findings reveal that the twelve ceramic sculpture receptacles incorporate culturally revered animals (birds, reptiles, amphibians, mammals) as decorative symbols. These animal-related metaphors are strongly tied to traditional Ghanaian society's sociocultural, religious, and political dimensions. These symbols reflect rich cultural values and philosophies, making the artefacts vital for preserving and promoting Ghanaian cultural heritage. The study recommends further research on other institutional artefacts to decode their embedded sociocultural repositories. This tends to promote and preserve Ghanaian cultural and artistic heritage, which serves as an educational tool for current and future generations.